2017
DOI: 10.1111/pce.12916
|View full text |Cite
|
Sign up to set email alerts
|

Rice calcium‐dependent protein kinase OsCPK17 targets plasma membrane intrinsic protein and sucrose‐phosphate synthase and is required for a proper cold stress response

Abstract: Calcium-dependent protein kinases (CDPKs) are involved in plant tolerance mechanisms to abiotic stresses. Although CDPKs are recognized as key messengers in signal transduction, the specific role of most members of this family remains unknown. Here we test the hypothesis that OsCPK17 plays a role in rice cold stress response by analyzing OsCPK17 knockout, silencing, and overexpressing rice lines under low temperature. Altered OsCPK17 gene expression compromises cold tolerance performance, without affecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 112 publications
(137 reference statements)
2
54
0
Order By: Relevance
“…As shown in Fig. 5, BdCDPK08was significantly upregulated in the seedlings by treatment with all test phytohormones, suggesting BdCDPK08 might play critical roles in phytohormones-induced signaling pathway, and execute multifunction in plant growth and development, which was consistent with the previous reports that the homologs of BdCDPK08 were played important roles in plant growth and development and response to abiotic and biotic stresses (Additional file 14) [32,[79][80][81][82][83]. It has been reported that CDPKs regulated ABA signal pathway by phosphorylating ABA-responsive element binding factors (ABFs) and ABA Insensitive (ABI).…”
Section: Expression Profile Of Bdcdpk Genessupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in Fig. 5, BdCDPK08was significantly upregulated in the seedlings by treatment with all test phytohormones, suggesting BdCDPK08 might play critical roles in phytohormones-induced signaling pathway, and execute multifunction in plant growth and development, which was consistent with the previous reports that the homologs of BdCDPK08 were played important roles in plant growth and development and response to abiotic and biotic stresses (Additional file 14) [32,[79][80][81][82][83]. It has been reported that CDPKs regulated ABA signal pathway by phosphorylating ABA-responsive element binding factors (ABFs) and ABA Insensitive (ABI).…”
Section: Expression Profile Of Bdcdpk Genessupporting
confidence: 91%
“…Lossof-function mutations of CPK4 and CPK11 exhibited pleiotropic ABA-insensitive phenotypes and decreased tolerance of seedlings to salt stress, further study showed that CPK4 and CPK11 positively regulated calciummediated ABA signaling pathways through the phosphorylation of two ABA-responsive transcription factors, ABF1 and ABF4 [28]. Over-expression of OsCDPK7 enhanced plant tolerance to salinity/drought by inducting some stress-responsive genes, but not to cold, while OsCDPK13 and OsCPK17 were supposed to be important signaling components for response to cold stress in rice [30][31][32]. Recent studies have provided compelling evidence for the involvement of CDPKs in immunity signaling and plant disease resistance.…”
Section: Introductionmentioning
confidence: 95%
“…This change in cytoplasmic Ca 2+ is sensed by calcium sensors such as calcium-dependent protein kinases (CPKs), which interact with downstream signaling components including hormones such as abscisic acid (ABA), reactive oxygen species (ROS), and mitogen-activated protein kinases (MPKs), leading to an increased tolerance to various stresses ( Boudsocq and Sheen, 2013 ). CPKs play an important role in signal transduction, and the functions of several CPKs in Arabidopsis and rice have recently been identified ( Almadanim et al , 2017 ; Jin et al , 2017 ). Activated CPKs participate in different signal transduction pathways through the phosphorylation of specific substrates ( Kobayashi et al , 2012 ; Santin et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…cv. Nipponbare mature seeds were used for rice transformations according to (Almadanim et al, 2017), and selection for transformants asserted by hygromycin resistance and standard GUS-staining with X-Gluc solution (Roth) of a section of seminal roots. Proteins were extracted, detected and quantified using a modified TCA/Acetone method (Luís et al, 2016).…”
Section: Methodsmentioning
confidence: 99%